Personality preferences and stress perception among nursing students in different nursing programmes: a cross-sectional study - Yuh-Shiow Li; Hui-Chen Tseng; Bao-Huan Yang; Mary Etta C. Mills; Wen-Pin Yu (BMC Medical Education)
Abstract Background Understanding personality preferences is crucial for guiding healthcare education and the stress management strategies of nursing students. While stress in nursing education has been well studied, its relationship with personality preferences, particularly in clinical settings, has been underexplored. This study aims to investigate the relationship between personality preferences and stress perception among nursing students in three different nursing programmes. Methods This cross-sectional study recruited 780 nursing students. We used structured questionnaires to collect data on demographics, personality preferences, and stress perception. The Myers–Briggs Type Indicator (MBTI) was used to measure personality preferences across four dimensions: extraversion/introversion, sensing/intuition, thinking/feeling, and judging/perceiving. The Chinese version of the MBTI and the Nurse Stress Checklist were also employed. Statistical analyses included descriptive statistics, one-way analysis of variance, and independent t-tests. Results Three common personality preferences were identified: extraversion, intuition, feeling, and perceiving; introversion, sensing, thinking, and judging; and introversion, sensing, feeling, and judging. The findings indicate that stress was significantly related to personality preferences. There were significant differences in the stress scores and the extraversion/introversion and thinking/feeling subscales. However, no significant differences in stress levels were observed across different nursing programmes. Conclusions Each personality trait exhibited specific stress coping mechanisms. Addressing students' stress is crucial because it can lead to academic burnout and attrition. This study's findings can inform strategies to reduce stress while accommodating students' personality traits, ultimately enhancing student success in nursing programmes.